Preferences of Accountancy Graduating Students of a CPA Review Center: A Conjoint Analysis Study - Rey Castillo; Enrico C. Yee, Jr. (UNUSA Press, 2023)
Conjoint Analysis was used in this study to ascertain the preferences of accountancy graduates from a CPA review institution in Davao City. The study also established the aggregate model and the relative importance of the CPA review center characteristics, including track record, reviewers, conduciveness, review materials, and affordability in contributing to the overall value of review centers. Based on the results,